2018
DOI: 10.1097/ico.0000000000001702
|View full text |Cite
|
Sign up to set email alerts
|

Anterior Segment Changes After Femtosecond Laser-Assisted Implantation of a 355-Degree Intrastromal Corneal Ring Segment in Advanced Keratoconus

Abstract: These findings may help explain the marked improvement in visual parameters obtained from the Keraring 355 degrees in advanced central keratoconus. In addition, these types of rings may be a safe, effective, and minimally invasive way to avoid corneal grafting in advanced keratoconus with a clear cornea.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 19 publications
0
8
1
1
Order By: Relevance
“…Most surgical nomograms rely upon the Journal of Ophthalmology axial map to determine the cone location or asymmetry. Instead of constructing a validated and reliable nomogram, simple unexplained instructions are provided with each ring [14][15][16]. Few attempts were reported to create validated nomograms or simulated models to avoid unpredictable events [17].…”
Section: Discussionmentioning
confidence: 99%
“…Most surgical nomograms rely upon the Journal of Ophthalmology axial map to determine the cone location or asymmetry. Instead of constructing a validated and reliable nomogram, simple unexplained instructions are provided with each ring [14][15][16]. Few attempts were reported to create validated nomograms or simulated models to avoid unpredictable events [17].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, Flecha-Lescún et al [57] theoretically hypothesized that implantation of the segments in the posterior corneal stroma could halt KCP while their implantation in the anterior corneal stroma could properly accelerate KCP. On the contrary, to this theory, Abd Elaziz et al [58] evaluated the implantation of 355° Keraring segment in the treatment of advanced KC with central cones. They concluded that this type of segment was effective and revealed marked visual and refractive improvements.…”
Section: Vascularization Opacificationmentioning
confidence: 99%
“…4 The benefits of ICRS have been established in the literature for the treatment of keratoconus, with much less risk involved, showing to be an effective and safe alternative for the treatment of the condition. [5][6][7][8][9] However, the intracorneal ring has been limited to eyes with Kmax (maximum keratometry) values less than 58 D, as larger curvatures could be associated with worse visual outcomes and more complications, such as extrusion. 10 Despite the existing studies on ring implants addressing the outcomes of intracorneal ring implantation in advanced keratoconus, these studies are limited to patients with maximum curvatures lower than 60D.…”
Section: Introductionmentioning
confidence: 99%
“…10 Despite the existing studies on ring implants addressing the outcomes of intracorneal ring implantation in advanced keratoconus, these studies are limited to patients with maximum curvatures lower than 60D. 8,11,12 This is the first study to show the results of the Ferrara ring of 320°o f arc (AJL, Vitoria, Spain) as an alternative therapy in patients with advanced keratoconus, grade IV, with Kmax > 60D, intolerant to contact lens, and with indication for corneal transplantation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation